2021
DOI: 10.1111/tra.12812
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidic acid‐PKA signaling regulates p38 and ERK1/2 functions in ligand‐independent EGFR endocytosis

Abstract: Ligand-independent epidermal growth factor receptor (EGFR) endocytosis is inducible by a variety of stress conditions converging upon p38 kinase. A less known pathway involves phosphatidic acid (PA) signaling toward the activation of type 4 phosphodiesterases (PDE4) that decrease cAMP levels and protein kinase A (PKA) activity. This PA/PDE4/PKA pathway is triggered with propranolol used to inhibit PA hydrolysis and induces clathrin-dependent and clathrin-independent endocytosis, followed by reversible accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 96 publications
(249 reference statements)
0
5
0
Order By: Relevance
“…Similar observations were reported for the borate exporter BOR1, in which AP-2-dependent and AP-2-independent endocytic routes had been activated by low and high borate concentration, respectively (Yoshinari et al, 2019). In mammals, the well-studied epidermal growth factor receptor (EGFR) is also internalized via multiple endocytic routes, including canonical ligand-dependent clathrin-mediated endocytosis and clathrin-independent endocytosis route, which both depend on the ligand concentration (Zhou and Sakurai, 2022), and a ligand-independent route where EGFR endocytosis is induced by stress conditions and does not require kinase activity or ubiquitination (Metz et al, 2021). Taken together, our results show that the BRI1 internalization is not abolished in the BR binding-deficient mutant, similarly to BRI1 YXXΦ endocytic motif mutants (Liu et al, 2020), the BRI1 ubiquitination-deficient mutants (Martins et al, 2015; Zhou et al, 2018) and the BRI1 endocytosis in AP-2 mutants(Di Rubbo et al, 2013; Gadeyne et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Similar observations were reported for the borate exporter BOR1, in which AP-2-dependent and AP-2-independent endocytic routes had been activated by low and high borate concentration, respectively (Yoshinari et al, 2019). In mammals, the well-studied epidermal growth factor receptor (EGFR) is also internalized via multiple endocytic routes, including canonical ligand-dependent clathrin-mediated endocytosis and clathrin-independent endocytosis route, which both depend on the ligand concentration (Zhou and Sakurai, 2022), and a ligand-independent route where EGFR endocytosis is induced by stress conditions and does not require kinase activity or ubiquitination (Metz et al, 2021). Taken together, our results show that the BRI1 internalization is not abolished in the BR binding-deficient mutant, similarly to BRI1 YXXΦ endocytic motif mutants (Liu et al, 2020), the BRI1 ubiquitination-deficient mutants (Martins et al, 2015; Zhou et al, 2018) and the BRI1 endocytosis in AP-2 mutants(Di Rubbo et al, 2013; Gadeyne et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the internalization of inactive EGFR is through a PA effector‐rolipram‐sensitive type 4 phosphodiesterase (PDE4) that mediated down‐regulation of protein kinase A (PKA) activity. The PA/PDE4/PKA pathway regulates p38 and ERK1/2 functions in ligand‐independent EGFR endocytosis [28]. PLD2 activity has been shown to be important for internalization of micro‐opioid receptors and metabotropic glutamate receptors [3].…”
Section: Pa As Dynamic Regulators Of Cell Functionsmentioning
confidence: 99%
“…Similar observations were reported for the borate exporter BOR1, in which AP-2-dependent and AP-2independent internalization had been activated by low and high borate concentration, respectively (Yoshinari et al, 2019). Equally in mammals, the well-studied epidermal growth factor receptor (EGFR) is also internalized via different endocytic mechanisms, including canonical liganddependent clathrinmediated endocytosis and clathrin-independent endocytosis, which both depend on the ligand concentration (Zhou and Sakurai, 2022), and a ligand-independent internalization where EGFR endocytosis is induced by stress conditions and does not require kinase activity or ubiquitination (Metz et al, 2021). However, after internalization, BRI1 and BRI1 Q pursued the same trafficking routes.…”
Section: Endocytosis Of Bri1 Is Independent Of Br Bindingmentioning
confidence: 99%